Security management manual - Encarnacion, Antonio M. (Quezon City, Philippines : Private Security Institute, 1985)
The book attempts to put these security principles, practices and ideas of USA authors on security management to fit Philippine setting as experienced by the Author in his almost fifteen years in the private security industry.
Part I. General security management -- Part II. Security personnel management -- Part III. Operational management -- Part IV. Public relations -- Appendices.
Keywords: MANAGEMENT -- SECURITY